A Scientometric Review of Environmental Valuation Research with an Altmetric Pathway for the Future - Olukolajo M.A.; Oyetunji A.K.; Amaechi C.V. (MDPI, 2024)
Environmental valuation (EV) research has advanced significantly as a method of assigning value to environmental goods, many of which lack readily discernible market values. The term environmental valuation describes a number of methods for putting monetary values on environmental effects, particularly non-market effects. Over the years, there has been a continuous increase in the number of publications on the topic. According to searches via the Scopus and Web of Science (WoS) databases, the phrase environmental valuation first occurred in 1987. The current research examines patterns in publishing rates over the previous three decades to analyse environmental valuation activity. To identify the future pathway, a research pattern was identified using Scopus, WoS, and the Altmetric Explorer. The data were postprocessed using VOSviewer to identify the mapping networks